2014
DOI: 10.1583/14-4795mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Endovascular Aneurysm Repair Using the Endurant Stent-Graft According to the Instructions for Use vs. Off-Label Conditions

Abstract: Off-label use of the Endurant stent-graft was associated with a greater but acceptable risk of type I endoleak. Otherwise, there was no difference between the IFU and off-label groups as regards survival, graft thrombosis, or reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…19 Globally, patients operated on in off-label conditions with Endurant stent graft have no statistically significant different early and midterm results with respect to those patients who have undergone treatment according to the instructions for use. 6,9 Off-label use of Endurant stent graft was associated with only a greater but acceptable risk of type I endoleak; this risk remained stable during the follow-up. 9 The focus on this new-generation device was always on the proximal aortic neck, except for one study in which the outcomes of this graft were evaluated in terms of limb occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Globally, patients operated on in off-label conditions with Endurant stent graft have no statistically significant different early and midterm results with respect to those patients who have undergone treatment according to the instructions for use. 6,9 Off-label use of Endurant stent graft was associated with only a greater but acceptable risk of type I endoleak; this risk remained stable during the follow-up. 9 The focus on this new-generation device was always on the proximal aortic neck, except for one study in which the outcomes of this graft were evaluated in terms of limb occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Off-label use of Endurant stent graft was associated with only a greater but acceptable risk of type I endoleak; this risk remained stable during the follow-up. 9 The focus on this new-generation device was always on the proximal aortic neck, except for one study in which the outcomes of this graft were evaluated in terms of limb occlusion. 20 van Zeggeren et al 20 reported that Endurant endograft occlusion occurred in 4.0% of about 500 unselected patients at a median follow-up of 1.7 years; a technical justification for occlusion has been found by a board of experts for about 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our institutions, the Endurant device is the preferable abdominal endovascular endoprosthesis for standard EVAR. 13,15 In addition, we have to underline that at least for the moment, use of the Endurant device for the chimney technique is outside of the instructions for use of the device. This should be considered in elective cases with the option to use other techniques.…”
Section: Discussionmentioning
confidence: 99%